Reconsidering Women’s ʿawrah after Menopause: A Maqāṣid al-Sharī‘ah Interpretation of QS al-Nūr [24]: 60 in Hannān Lahhām’s Tafsīr - Maycilia, Santi; Fajria, Nura; Al Wasim, Arif; Husna, Ikmely Dina Nuril (QOF, 2026)
Studies on women’s ʿawrah, particularly concerning postmenopausal women, remain relatively limited and are predominantly framed within normative juridical discussions. Yet the biological and social transformations accompanying menopause call for a more contextual and purposive interpretation of Qur’anic guidance. This article examines the interpretation of QS al-Nūr [24]:60 in Min Hadyi Sūrat al-Nūr by Hannān Lahhām through the framework of maqāṣid al-sharī‘ah, with particular attention to the ethical and tarbawī dimensions of his exegesis. The novelty of this study lies in its examination of postmenopausal women as a distinct legal and ethical subject in the Qur’an and its reconstruction of rukhṣah as a form of ethical reasoning rather than a mere legal exception. Employing a qualitative library research method, the study draws upon Lahhām’s tafsir as its primary source, supplemented by classical and contemporary works of tafsir and Islamic legal thought. The findings demonstrate that Lahhām interprets the concession granted in QS al-Nūr [24]:60 not as unrestricted permissibility, but as an ethically guided accommodation that remains grounded in the values of ʿiffah (chastity), ḥayāʾ (modesty), and the preservation of human dignity. Through a maqāṣid-oriented reading, the verse recognizes postmenopausal women as a distinct legal subject whose changing biological and social circumstances warrant a proportional adjustment of legal expectations while maintaining moral coherence. Consequently, Lahhām’s interpretation illustrates the adaptive and purposive character of Qur’anic law, demonstrating how legal flexibility safeguards human welfare and dignity in changing social contexts.